Secular trends in antihyperglycaemic medication prescriptions in older adults with diabetes and chronic kidney disease: 2004–2013. Issue 6 (12th April 2016) - Clemens, K. K.; Liu, K.; Shariff, S.; Schernthaner, G.; Tangri, N.; Garg, A. X.
Abstract : Aim: To examine how antihyperglycaemic medications were prescribed to older adults with diabetes and chronic kidney disease over the last decade. Methods: We conducted a population‐based study of 144 252 older adults with diabetes and chronic kidney disease (estimated glomerular filtration rate <60 ml/min/1.73 m 2 or receiving chronic dialysis) in Ontario, Canada. In each study quarter (3‐month intervals from 1 April 2004 until 31 March 2013) we studied the proportion of treated and newly treated patients prescribed insulin, sulphonylureas, α‐glucosidase inhibitors, metformin, thiazolidinediones, meglitinides and dipeptidyl peptidase‐4 (DPP‐4) inhibitors. We further examined prescription trends by stage of chronic kidney disease. Results: The mean age of patients increased slightly (from 76 to 78 years) over the study period and the percentage with comorbidities declined. Metformin was the predominant therapy prescribed (prescribed to a mean of 56.1% of treated patients). Glyburide (glibenclamide) and thiazolidinedione prescriptions decreased (glyburide prescriptions declined from 45.5 to 9.5%, rosiglitazone from 3.6 to 0.2% and pioglitazone from 1.9 to 1.7%), while gliclazide and DPP‐4 inhibitor prescriptions increased (gliclazide prescriptions increased from 0.6 to 26.4%, sitagliptin from 0 to 15.3% and saxagliptin from 0 to 2.0%). Up to 48.6% of patients with stage 3a–5 chronic kidney disease or receiving chronic dialysis were prescribed glyburide, and up to 27.6% of patients with stage 4–5 disease or receiving chronic dialysis were prescribed metformin. Conclusions: In patients with chronic kidney disease, there were trends towards safer antihyperglycaemic medication prescribing. A considerable number of patients, however, continue to receive medications that should be avoided.